The use of topical calcineurin inhibitors in chronic wound management - Geoff Sussman (Wound Practice and Research, 2018)
The management of wounds has evolved over many years and with a greater understanding of the mechanisms of skin repair, a recent approach to treatment is to address the changes in tissue. Complex chronic wounds place a significant challenge on health professionals working with these patients, in accurately identifying the underlying cause of the wound and the tissue factors impacting on wound healing. Many different types of dressings are used with limited success; however, dressings do not address the imbalances in tissue. Once a clear diagnosis has been established, the approach is to try to address this underlying imbalance in the tissues. Calcineurin inhibitors were approved for topical use in 2000–2001 for the treatment of atopic dermatitis. Since that time, their use has expanded to treat a number of chronic wounds, including pyoderma gangrenosum, cutaneous lupus erythematosus and other uncommon chronic wounds, with some success. This approach, in contrast to dressings that only impact on the wound environment, addresses the need to restore tissue balance and thus encourage wound healing.